1998
DOI: 10.1161/01.res.83.3.322
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Expression of Lectin-like Oxidized LDL Receptor-1 in Vascular Endothelial Cells

Abstract: Endothelial dysfunction, or activation, elicited by oxidized LDL (Ox-LDL) or its lipid constituent, has been implicated in the initiation and progression of atherosclerosis. We have recently identified a C-type lectin-like molecule, designated lectin-like Ox-LDL receptor-1 (LOX-1), which acts as a cell-surface receptor for Ox-LDL in cultured vascular endothelial cells. In this study, we provide evidence that LOX-1 expression can be upregulated by tumor necrosis factor-alpha (TNF-alpha) and phorbol 12-myristate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
187
1
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 289 publications
(198 citation statements)
references
References 36 publications
5
187
1
5
Order By: Relevance
“…Kume et al (1998) showed that TNF-α increases LOX-1 expression in a concentration-dependent manner in bovine aortic endothelial cells. The time-course experiments showed that LOX-1 mRNA levels peaked at 2 hours and remained elevated for at least 21 hours.…”
Section: Enhancement Of Lox-1 Expression By Atherosclerosis-related Rmentioning
confidence: 99%
“…Kume et al (1998) showed that TNF-α increases LOX-1 expression in a concentration-dependent manner in bovine aortic endothelial cells. The time-course experiments showed that LOX-1 mRNA levels peaked at 2 hours and remained elevated for at least 21 hours.…”
Section: Enhancement Of Lox-1 Expression By Atherosclerosis-related Rmentioning
confidence: 99%
“…21 Studies on the regulation of LOX-1 expression in EC, M⌽, and SMC revealed upregulation of LOX-1 expression after incubation with PMA, 16,17,19 an activator of PKC. Our study also showed a 3-fold upregulation of LOX-1 mRNA and protein expression after incubation with PMA, comparable with the detected upregulation of LOX-1 expression after incubation with IL-1␣, IL-1␤, and TNF.…”
Section: Lox-1 Expression Is Upregulated By Proinflammatory Cytokinesmentioning
confidence: 99%
“…15 Atherosclerotic lesions containing lipid-laden foam cells are the hallmark of the inflammatory state, and recent investigations showed that inflammatory stimuli modulate LOX-1 expression in vitro. IL-4 induces LOX-1 expression in M⌽ 16 and tumor necrosis factor (TNF)-␣ and transforming growth factor (TGF)-␤ upregulate LOX-1 expression in EC, 17,18 M⌽, 18 -20 and SMC. 18,19 Activation of protein kinase C (PKC), which plays a central role in mediating inflammatory responses, 21 upregulates LOX-1 expression in EC, 17 M⌽, 16,19 and SMC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 LOX-1 is a single transmembrane domain protein with its carboxyl-terminal end containing an extracytoplasmic C-type lectin domain, and is expressed in various cells, including endothelial cells, macrophages, vascular smooth muscle cells, and dendritic cells. 3,[5][6][7] Expression of LOX-1 is enhanced by oxidative stress, 8 stimulation by mediators of inflammation such as IL-1b 9,10 and tumor necrosis factor (TNF)-a, 11 its ligand ox-LDL, 12 and fluid shear stress. 13 In rat zymosan-induced arthritis, induction of the expression of LOX-1 was accompanied by accumulation of ox-LDL in chondrocytes, suggesting the possible interaction of ox-LDL and LOX-1 in cartilage.…”
Section: Introductionmentioning
confidence: 99%